Drug discovery in Focal and Segmental Glomerulosclerosis - Pullen, Nick (Kidney Int, 2016)
Despite the high medical burden experienced by patients with focal segmental glomerulosclerosis (FSGS), the etiology of the condition remains largely unknown. FSGS is highly heterogeneous in clinical and morphological manifestations. While this presents challenges for the development of new treatments, research investments over the last two decades have yielded a surfeit of potential avenues for therapeutic intervention. The development of many of those ideas and concepts into new therapies, however, has been very disappointing. Here, we describe some of the factors that have potentially contributed to the poor translational performance from this research investment, including the confidence we ascribe to a target, the conduct of experimental studies, and the availability of selective reagents to test hypotheses. We will discuss the significance of genetic and systems traits as well as other methods for reducing bias. We will analyze the limitations for a successful drug development. We will use specific examples hoping that these will guide a consensus for investment and drive greater translational quality. We hope that this substrate will serve to exemplify the tremendous opportunity for intervention as well as facilitate greater collaborative effort between industry, academia and private foundations in promoting appropriate validation of these targets. Only then will we have achieved our goal for curative therapies for this devastating disease.